Optimization of Poultry Feed Formulation Using Experimental Design Methodology - K.Y., Inoussa; PARKOUDA, Charles; SOMDA, Marius K.; DIAWARA, Bréhima; DICKO, Mamoudou H. (International Journal of Poultry Science, 2021)
Objective: This study was carried out to deal with reducing feed cost and provide high quality poultry feed for the local breed of chickens “Poulet du Faso”. Materials and Methods: In this study the modeling based on the mixed design technique was used. The local raw materials used for this feed were selected on the basis of their biochemical composition, availability and accessibility. Results: The optimization of first degree polynomial equation yielded an optimal formulation composed of corn (40%, w/w), cottonseed meal (5%, w/w), soybean meal (15%, w/w), wheat bran (5%, w/w), rice bran (11.63%, w/w), fish meal (13.12%, w/w), oyster shell (2.5%, w/w), bi-calcium phosphate (2.5%, w/w), iodized salt (0.25%, w/w) and mineral-vitamin-nitrogen concentrate (CMVA) (5%, w/w). This formula has increased the average daily gain from 9.23-29.97 g and lowered the feed cost to 30%, with an overall desirability index of 88.05%. Conclusion: The obtained optimal formulation will considerably reduce the rearing time, minimize the cost of production and consequently increase the profit margin.